EVALUASI SISTEM PELAYANAN PUBLIK DIGITAL DALAM MEWUJUDKAN GOOD GOVERNANCE: STUDI KASUS SIGAP DAN SIADEK KANTOR DESA KUTUH, KUTA SELATAN, BALI - Ni Ketut Eka Muliani; Natalia Gersia Elan (Nusantara Hasana Journal, 2025)
This study analyzes the effectiveness of digital public service implementation in realizing the principles of Good Governance at the village level. Located in Kutuh Village, South Kuta, Bali, this research uses a case study of the use of the Government Administration Geographic Information System (SIGAP) and the Kutuh Village Administration Information System (SIADEK). The main objective was to examine the implementation strategy, the impact perceived by the community, and the contribution of the digital system to the principles of transparency, accountability, efficiency, and participation. Qualitative research methods were used, with data collection techniques including interviews, observation, and document analysis. The results revealed that successful implementation strategies included technological infrastructure modernization, human resource training (village officials), and community outreach. The resulting impacts proved positive, characterized by more efficient, accountable, and transparent services, and increased citizen engagement. However, several challenges remain that need to be addressed. For future optimization, this study recommends the importance of sustainable infrastructure investment, ongoing training for officers, regular evaluation, and strategic collaboration with third parties.